Well-Defined Conjugated Macromolecules Based on Oligo(Arylene Ethynylene)s in Sensing - Agata Krywko-Cendrowska (Processes, 2020)
Macromolecules with well-defined structures in terms of molar mass and monomer sequence became interesting building blocks for modern materials. The precision of the macromolecular structure makes fine-tuning of the properties of resulting materials possible. Conjugated macromolecules exhibit excellent optoelectronic properties that make them exceptional candidates for sensor construction. The importance of chain length and monomer sequence is particularly important in conjugated systems. The oligomer length, monomer sequence, and structural modification often influence the energy bang gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the molecules that reflect in their properties. Moreover, the supramolecular aggregation that is often observed in oligo-conjugated systems is usually strongly affected by even minor structural changes that are used for sensor designs. This review discusses the examples of well-defined conjugated macromolecules based on oligo(arylene ethynylene) skeleton used for sensor applications. Here, exclusively examples of uniform macromolecules are summarized. The sensing mechanisms and importance of uniformity of structure are deliberated.